De Brusselse metropool: naar een ontwikkelingsmodel tussen dat van Rijsel en Berlijn? - Caroline Van Wynsberghe (Brussels Studies, 2007)
The least known of the different scenarios being debated for Brussels are probably those for the development of a metropolis or an urban community. In their minimalist versions, both scenarios can be envisaged without requiring institutional reform and without touching the borders of Brussels, which makes them less “onbespreekbaar” – depending on the interlocutor – than enlargement of the city, co-management, or the European district. Lille’s development is based on two territories: the urban community that groups 85 municipalities and the metropolis that transcends state borders. Berlin and Brandenburg have explored a merger, but the project was blocked by a referendum. However, various types of formal “metropolitan”-type cooperation have been put in place. The four scenarios resulting from these two cities offer lessons for the development of Brussels.